Do local investors know more? Evidence from securities class actions - Kim, Taeyeon; Hwang, Hyoseok (David); Kim, Hyun-Dong (Journal of Banking & Finance, 2023)
This paper explores the informed trading by mutual funds of local investments. Using hand-collected securities class actions (SCAs), we examine whether local mutual funds can avoid potential economic damage from SCAs against their portfolio firms by selling them in advance – local information advantage hypothesis. Our findings are consistent with the hypothesis. The informed selling by local funds of the SCA firms is driven by the firms with low analyst coverage and high forecasting errors, which suggests that local funds benefit the most when an SCA firm's information environment is poor. Furthermore, we find that informed trading of local funds can predict a possible outcome of the lawsuit. Finally, the magnitude of informed selling is greater when firms are closer to local funds and the class period is shorter.